Perbedaan Fase Pendidikan Kedokteran terhadap Persepsi tentang Informed Consent - Haniefa, Diena; Wujoso, Hari; Suwandono, Adji (Nexus Kedokteran Klinik, 2014)
Background: Medical Education Phases are divided into two phases, both are preclinical phase and clinical phase where in the clinical phase, students get clinical experiences. Experience is one factor that affects the formation of perceptions. From 2006 through 2012, Indonesian Medical Disciplinary Board (MKDKI), has received 183 complaints lodged with 5 problems related medical services in Indonesia, one of which is a communication problem. This study aims to determine the difference of medical education phases concerning perceptions of informed consent Methods: This study is an observational study with cross-sectional design which was held on December 2013 at the Faculty of Medicine, Sebelas Maret University and Dr. Moewardi Hospital, Surakarta. 60 subjects were taken by purposive sampling method continued with convenience sampling method. Subjects were asked to fill out a form of identity, informed consent sheet and questionnaire. Then the results of the questionnaire were tested by the Independent t-test through SPSS 20.0 for Windows. Results: Preclinical students were 30 respondents (50 %) , and clinical studentsÂ  were 30 respondents (50 %) . The results of the analysis by the Independent t- test showed no difference medical education phases (p = 0.083) concerning perceptions of informed consent. Conclusion: There were no difference medical education phases concerning perceptions of informed consent. Keywords: Medical Education Phases, Perception, Informed ConsentÂ